Student Teacher of Malay Language as a First Language: Do They Have the Confidence to Teach - Jamian, Abdul Rasid; Konting, Mohd Majid; Bakar, Ab. Rahim (The International Journal of Learning, 2007)
The objective of the study was to assess the teaching confidence of student teacher who’s specialization is Teaching of Malay as a First Language. The specific objectives were to determine the teaching confidence in terms of student engagement; instructional strategies; classroom management and teaching with computers in classroom. Data were gathered from a sample of 53 student teachers. Findings indicate that a majority of the respondents had a high level of confidence in terms of student engagement (Mean: 3.97, S.D: 0.29), instructional strategies (Mean: 3.93, S.D: 0.38), classroom management (Mean: 3.90, S.D: 0.32) and teaching with computers in classroom (Mean: 3.83, S.D: 0.57).